ANALISA SIMPANG TIGA TAK BERSINYAL MENGGUNAKAN MANAJEMEN LALU-LINTAS (STUDI KASUS SIMPANG TIGA BAJAK) - Chesi Anggraini; Hardiansyah Hardiansyah; Makmun R. Razali (Inersia: Jurnal Teknik Sipil, 2019)
The purpose of this study was to determine the level of performance at Intersection Three  Bajak depicted of the degree of saturation (DS), delay, queue opportunities. In this study using the program KAJI and MKJI 1997 as a reference in data processing. In this study there are two alternative solutions to problems that bans the installation of stop signs (alternative 1) and unsignalised intersection improve ments to the signalized intersection (alternative 2). Based on field surveys conducted for 4 (four) days are Monday, Tuesday, Saturday and Sunday, the result degree of saturation at maximum traffic flow from observation days more from the requredment line of MKJI 1997 is ? 0,8 pcu/h exccept at Sunday. As a example for accounting is used maximum traffic flow was at Tuesday with capacity is 2726 smp/jam. From the analysis for the exsisting condition at Intersection Three Bajak produce the degree of saturation (DS) is 0,975 pcu/h, this result more from the requredment line of MKJI 1997 is ? 0,8 pcu/h. Delay that occurs for the exisisting condition is 17,96 sec/pcu and Queue opportunities generated in the exsisting conditions is 38% - 75 %. Alternative condition 1 of produce the degree of saturation (DS) is 0.965 pcu/h was still more from the requredment line of MKJI 1997. Delay is 17,57 sec/pcu and Queue opportunities is 37% -77%. Alternative condition 2 produce the degree of saturation (DS) for Bali street is 0,655 pcu/h, MT. Haryono street is 0,621 pcu/h, Jawa street is 0,693 smp/jam, these results are consistent with the requredment line of MKJI 1997 is ? 0.80. Delay for Bali street is 22,33 sec/pcu, MT. Haryono street is 18,54 sec/pcu and Jawa street is 29,13 sec/pcu. Judging from the degree of saturation (DS), alternative 2 was accordance with the requredment line of MKJI so that it can be concluded that the improvement of the unsignalised intersection to signalized intersection the best alternative solutions to Intersection Three Bajak. Based on exsisting condition, level of service Intersection Three Bajak on level E and degree of saturation is 0,85-1,00 pcu/h.